White-toothed shrews (Mammalia, Soricomorpha, Crocidura) of coastal islands of Vietnam - Abramov, Alexei V. (Pensoft Publishers, 2012)

(untitled)
Abstract. New findings of the white-toothed shrews (Crocidura spp.) from offshore islands of Vietnam are reported. The species identifications have been confirmed by the analysis of complete mitochondrial cytochrome b gene (1140 bp). Crocidura phuquocensis is the only species found in the Phu Quoc Island. Crocidura fuliginosa has been recorded from two islands of the Con Dao Archipelago (Con Son and Bai Canh). The occurrence of Crocidura fuliginosa in Vietnam has been genetically confirmed for the first time. Crocidura attenuata has been collected from the Cat Ba Island for the first time, and this finding corresponds well with the proposal that the species’ distribution is confined to the north and east of the Red River only.